2006
DOI: 10.1089/acm.2006.12.389
|View full text |Cite
|
Sign up to set email alerts
|

Colonic Irrigations: A Review of the Historical Controversy and the Potential for Adverse Effects

Abstract: Colonic irrigations enjoy widespread popularity in the alternative medicine community, while being viewed with considerable skepticism by the conventional medical community. While proponents make claims of substantial health benefits, skeptics cite the lack of evidence for health benefits, and emphasize the potential for adverse effects. Yet historically, there are clinical reports of effectiveness, and virtually no research refuting these reports. Instead there was a campaign against exaggerated claims by non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 91 publications
0
9
0
Order By: Relevance
“…According to the ancient theory of “autointoxication,” the colon is believed to be a sewage system where by-products of incomplete digestion and toxins accumulate, and possibly poison the body resulting in various diseases [13]. Hence, some traditional physicians recommend routine treatment by the enema, a procedure involving the infusion of water or other fluids into the colon through the anus, in order to shorten the contact time of the toxins in the colon [4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…According to the ancient theory of “autointoxication,” the colon is believed to be a sewage system where by-products of incomplete digestion and toxins accumulate, and possibly poison the body resulting in various diseases [13]. Hence, some traditional physicians recommend routine treatment by the enema, a procedure involving the infusion of water or other fluids into the colon through the anus, in order to shorten the contact time of the toxins in the colon [4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…7 Thus, the coffee enema is claimed to have a very specific purpose in lowering serum toxins. 8 It has also been shown that substances found in coffee, for instance kahweol and cafestol, are potent enhancers of glutathione S-transferase (GST), a major antioxidant enzyme that catalyses the binding of a vast variety of electrophiles in the blood stream to the sulfhydryl group of glutathione (GSH). 9 In mice, for example, coffee beans enhance this system by 600% in the liver and 700% in the bowel.…”
Section: Introductionmentioning
confidence: 99%
“…The treatment is based on the ancient but obsolete theory of 'autointoxication', i.e. the body is assumed to poison itself with, 'autotoxins' which, in turn, cause various illnesses (2).…”
Section: Introductionmentioning
confidence: 99%
“…The treatment usually involves the administration of about ½ L of warm, filtered water through a proctoscope by means of an inflow ⁄ outflow intermittent flush out method (3). The purpose of this procedure is 'to infuse the entire colon with water, in contrast to the more limited infusion water in an enema' (2). Sometimes, ingredients such as herbal extracts are added to the water.…”
Section: Introductionmentioning
confidence: 99%